2020
DOI: 10.3390/su12041318
|View full text |Cite
|
Sign up to set email alerts
|

How Do International M&As Affect Rival Firm’s Sustainable Performance? —Empirical Evidence from an Emerging Market

Abstract: International mergers and acquisitions (M&As) have been increasingly used by emerging market enterprises (EMEs) as a springboard for strategic assets to overcome latecomer disadvantages and build sustainable competitive advantages. While current literature only focuses on the M&As’ impacts on acquirers, little is known about the impacts of EMEs’ international M&As on their external stakeholders, such as rival firms. Based on the longitudinal data covering 325 large international M&As completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
(98 reference statements)
1
8
0
Order By: Relevance
“…Gross-Gołacka et al attempted to improve the sustainable competitive advantage for enterprises by improving the knowledge ability of managers [8]. Hu et al argued industry-level international mergers and acquisitions had a significant negative impact on the sustainable performance of the acquirer's competitors [9]. Erokhin et al established policy measures to competitive advantages in agricultural field [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross-Gołacka et al attempted to improve the sustainable competitive advantage for enterprises by improving the knowledge ability of managers [8]. Hu et al argued industry-level international mergers and acquisitions had a significant negative impact on the sustainable performance of the acquirer's competitors [9]. Erokhin et al established policy measures to competitive advantages in agricultural field [10].…”
Section: Introductionmentioning
confidence: 99%
“…ere have been many reports on the research of core technical capabilities. Jin et al (2020) considered the impact of cluster technology innovation capability on the long-term development of the cluster, and found that the improvement of cluster technology innovation capability promoted the development of the industry [13]. Zhou et al used theory to create a theoretical framework of data-based core technical capabilities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study by Pradhan (2010) points out that Indian pharmaceutical firms' cross-border acquisition seeks both market expansion and strategic assets. A recent study by Hu et al (2020) suggests an interesting conclusion from observations of Chinese manufacturing firms' M&As for the period of 2009 to 2015; cross-border M&As have negative impacts on buyers' rival companies, particularly in high-tech industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Chinese firms need not develop every advanced technology on their own in a globalized world. Backed by the government’s “go global” strategy, they can acquire such technologies through mergers and acquisitions abroad ( Figure 10 ; Hu et al , 2020 ; Liu et al , 2020 ).…”
Section: Five Main Impetus For China’s Fast-growing In Technological Innovationmentioning
confidence: 99%